2019
DOI: 10.1111/desc.12920
|View full text |Cite
|
Sign up to set email alerts
|

Four‐year‐olds incorporate speaker knowledge into pragmatic inferences

Abstract: Human communication relies on the ability to take into account the speaker's mental state to infer the intended meaning of an utterance in context. For example, a sentence such as 'Some of the animals are safe to pet' can be interpreted as giving rise to the inference 'Some and not all animals are safe to pet' when uttered by an expert. The same inference, known as a scalar implicature, does not arise when the sentence is spoken by someone with partial knowledge. Adults have been shown to derive scalar implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…While our data do not demonstrate definitively that the cognitive tools used to calculate pragmatic inferences are general to language and non-linguistic communicative acts, our data are broadly consistent with this possibility, and are consistent with previous work that has shown that adults also can compute scalar inferences over visual stimuli (Kampa & Papafragou, 2020). While at least one previous study attempted to detect evidence that children could compute pragmatic inferences over non-linguistic stimuli (and found failure), even the authors of this study noted that children's failures were more likely due to "features of the task" than to a failure to use the tools of pragmatic inference outside the domain of language (Kampa & Papafragou, 2020).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…While our data do not demonstrate definitively that the cognitive tools used to calculate pragmatic inferences are general to language and non-linguistic communicative acts, our data are broadly consistent with this possibility, and are consistent with previous work that has shown that adults also can compute scalar inferences over visual stimuli (Kampa & Papafragou, 2020). While at least one previous study attempted to detect evidence that children could compute pragmatic inferences over non-linguistic stimuli (and found failure), even the authors of this study noted that children's failures were more likely due to "features of the task" than to a failure to use the tools of pragmatic inference outside the domain of language (Kampa & Papafragou, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…By framing the computation of pragmatic inferences more generally-and by grounding it outside the field of scalar implicature-we also open ourselves up to a tantalizing possibility: that pragmatic inferences may not be specific to language at all. While this possibility isn't new (Fan et al, 2020;Kampa & Papafragou, 2020;Sperber & Wilson, 1986), it is wildly understudied. Critically, if we are to develop robust theories of communication, we must understand the extent to which communicative inferences are restricted to the domain of language.…”
Section: Research Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, while these tasks are often taken as a “gold standard” for Theory of Mind, they measure False Belief, which is only one aspect of mentalising, and may not be required for implicatures in a simple communicative situation such as in our picture-matching task. An approach which could offer clearer interpretation of results would involve experimental manipulation of Theory of Mind within a pragmatic inferencing task, such as manipulating whether or not the speaker is knowledgeable (for adults see Breheny et al, 2013; and for paradigms suitable for children see Kampa & Papafragou, 2020, and Wilson et al, under revision).…”
Section: Discussionmentioning
confidence: 99%
“…& Tomasello, 2012; Kampa & Papafragou, 2020;Khu et al, 2020;Mazzarella & Pouscoulous, 2020;Nadig & Sedivy, 2002;Nilsen & Graham, 2009;. Thus, humans have well-established and early developing capacities to track what someone saw, experienced or is aware of; we will refer to this capacity as "simple knowledge tracking".…”
mentioning
confidence: 99%